The Effect of Supervision and Work Discipline on Motivation And Its Impact on The Performance of Public Elementary School Teachers in The Pulau Rimau District - Rita Anggraini; Taufani C Kurniatun; Lina Novita (Journal of Educational Sciences, 2026)
This study analyzes the effect of supervision and work discipline on teacher motivation and their impact on the performance of public elementary school teachers in Pulau Rimau District. The study was motivated by indications of low motivation, discipline, and performance among some teachers, which affected learning quality. A quantitative approach with a causal associative design was employed. The population consisted of all public elementary school teachers in the district, and total sampling was applied. Data were collected through questionnaires and analyzed using path analysis with SmartPLS. The findings reveal that supervision and work discipline do not have a significant direct effect on teacher motivation or performance, as indica ted by p-values greater than 0.05. However, motivation shows a positive and significant effect on teacher performance, with a path coefficient of 0.929 and a p-value below 0.05. These results indicate that motivation is the primary determinant of teacher performance, while supervision and discipline influence performance indirectly through motivation. Therefore, efforts to improve teacher performance should prioritize strategies that enhance intrinsic motivation through continuous support, rewards, and guidance.